(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Background Cardiovascular disease is increasingly recognized as an important complication among people living with HIV (PLWH). HIV infection is associated with accelerated atherosclerosis due to chronic immune activation, systemic inflammation, endothelial dysfunction, metabolic abnormalities, and prothrombotic changes with interruption of antiretroviral therapy (ART) may increase the risk of premature coronary artery disease (1,2). With the widespread availability of antiretroviral therapy (ART), PLWH have increased life expectancy; however, cardiovascular disease has emerged as an important cause of morbidity and mortality. Acute coronary syndrome (ACS) in young adults with HIV remains uncommon but carries significant morbidity and mortality. Case Presentation A 25-year-old male with known HIV infection presented with an 8-hour history of acute chest discomfort. The patient had a history of poor adherence to antiretroviral therapy and was considered to have uncontrolled HIV infection. Initial evaluation revealed electrocardiographic abnormalities with T-wave inversion suggestive of myocardial ischemia. Cardiac biomarkers were elevated, with troponin level of 1.6 (assay-dependent units), confirming myocardial injury. Echocardiography demonstrated regional wall motion abnormalities consistent with ischemic myocardial dysfunction. The patient was diagnosed with non–ST elevation myocardial infarction (NSTEMI) and admitted to the intensive cardiac care unit (ICCU). Despite appropriate acute management, the patient deteriorated rapidly and died several hours after admission. Conclusion This case highlights the occurrence of fatal NSTEMI in a very young patient with untreated HIV infection. Early cardiovascular risk assessment, optimization of ART adherence, and increased awareness of ACS among young PLWH are essential, particularly in low- and middle-income countries where access to advanced cardiac investigation and intervention may be limited such as Timor Leste.